2014
DOI: 10.1007/s11051-014-2690-x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology- and size-dependent spectroscopic properties of Eu3+-doped Gd2O3 colloidal nanocrystals

Abstract: The synthesis, morphological characterization, and optical properties of colloidal, Eu(III) doped Gd2O3 nanoparticles with different sizes and shapes are presented. Utilizing wet chemical techniques and various synthesis routes, we were able to obtain spherical, nanodisk, nanotripod, and nanotriangle-like morphology of Gd2O3:Eu3+ nanoparticles. Various concentrations of Eu3+ ions in the crystal matrix of the nanoparticles were tested in order to establish the levels at which the concentration quenching effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…In reality, gadolinium was never found as a pure free metal in nature up to present, so the most common chemical form the gadolinium oxide (Gd 3+ ) is considered. Currently, this oxide is effectively employed in other equally important applications, e.g., magnetic resonance and fluorescence imaging [2], fabrication of the base for Judd-Ofelt high-efficiency luminescent devices [3], doping-modification of thermally treated nanocomposites [4], semi-commercial manufacturing of magnetocaloric materials [5][6], etc. These abundant and promising applications of Gd 2 O 3 appear to be directly linked with its high chemical activity and structural specificity.…”
Section: Introductionmentioning
confidence: 99%
“…In reality, gadolinium was never found as a pure free metal in nature up to present, so the most common chemical form the gadolinium oxide (Gd 3+ ) is considered. Currently, this oxide is effectively employed in other equally important applications, e.g., magnetic resonance and fluorescence imaging [2], fabrication of the base for Judd-Ofelt high-efficiency luminescent devices [3], doping-modification of thermally treated nanocomposites [4], semi-commercial manufacturing of magnetocaloric materials [5][6], etc. These abundant and promising applications of Gd 2 O 3 appear to be directly linked with its high chemical activity and structural specificity.…”
Section: Introductionmentioning
confidence: 99%
“…wide bandgap (i.e., fully transparent in the visible region) oxides capable of being doped with lanthanide ions and possessing twophoton or multiphoton absorption properties. [106] In particular, a new approach based on 1D YVO 4 NPs for optical probes was demonstrated that utilizes near infrared to visible upconversion through multi-photon induced f-f emission of Eu 3+ doped nanorods. [107] The femtosecond open-aperture Z-scan measurements for undoped and doped YVO 4 demonstrated coexistence of two-and three-photon absorption processes at 650 nm, and four-and five-photon processes at 1300 nm.…”
Section: D/1d Materialsmentioning
confidence: 99%
“…This quenching mechanism is connected with the concentration of the active luminescence cations, and it is therefore known as concentration quenching. It is influenced by the nature of the material, the nature of the dopant and its distribution and by the NP morphology [196,197]. An optimization of the doping level is therefore required in order to obtain the nanophosphor with the highest emission intensity.…”
Section: Luminescent Properties Of Ln-doped Nanophosphors: Downconvermentioning
confidence: 99%